A measurement of top quark pair and photon production cross section with CMS detector - Makouski, Mikhail (Kansas State University, 2015)
In this thesis the measurement of production cross section of top-quark pairs in association with a photon in proton-proton collisions at a center of mass energy of 8 TeV is presented. The data was recorded at the CMS experiment at the LHC in 2012. This measurement aims to extend our knowledge of top quark properties and help to test consistency of the Standard Model (SM) of particle physics. Data-driven methods are used to estimate the photon identification efficiency and purity. The measured cross-section agrees with the standard model expectation.
Keywords: Large Hadron Collider; Top quark; Standard Model of particle physics; Particle Physics (0798)